2019
DOI: 10.1007/s13197-019-04164-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic ultra-high pressure homogenization on the structure and functional properties of whey protein

Abstract: The effects of dynamic ultra-high pressure homogenization (UHPH) on the structure and functional properties of whey protein were investigated in this study. Whey protein solution of 10 mg/mL (1% w/w) was prepared and processed by a laboratory scale high pressure homogenizer with different pressures (25, 50, 100, 150, 200, and 250 MPa) at an initial temperature of 25 °C. Then, the solution samples were evaluated in terms of secondary structure, sulfhydryl and disulfide bond contents, surface hydrophobicity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 32 publications
(23 reference statements)
3
16
0
Order By: Relevance
“…This indicates that some hydrogen bonds stabilising the protein secondary structure were disrupted during HPH treatment, leading to partial denaturation and unfolding of the protein molecules, unfolding the ordered structure of the protein, and an increase in the disordered system (Xu et al ., 2017). The rise of β‐sheet and β‐turn content indicated that HPH promoted the exposure of hydrophobic active sites and protein–protein hydrophobic interactions in the soy protein structure, which was beneficial in accelerating the formation of soluble aggregates in the denatured soybean protein molecule (Wang et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that some hydrogen bonds stabilising the protein secondary structure were disrupted during HPH treatment, leading to partial denaturation and unfolding of the protein molecules, unfolding the ordered structure of the protein, and an increase in the disordered system (Xu et al ., 2017). The rise of β‐sheet and β‐turn content indicated that HPH promoted the exposure of hydrophobic active sites and protein–protein hydrophobic interactions in the soy protein structure, which was beneficial in accelerating the formation of soluble aggregates in the denatured soybean protein molecule (Wang et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Sulfhydryl is the most active amino acid side-chain group of protein degradation [ 20 ]. The protein oxidation level is always evaluated by the abundance of free sulfhydryl and disulfide bonds [ 17 , 21 , 22 ]. The free sulfhydryl content decreased significantly, and the disulfide bond content increased significantly in the stored samples ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It manifested that HPH treatment induced the fracture of myofibrillar protein aggregates. Many studies stated that intense mechanical forces could cause the size reduction of protein aggregate, such as clam protein isolate (Wu et al., 2019b), cod protein (Ma et al., 2019), whey protein (Wang et al., 2020) and hazelnut meal proteins (Sarıcaoğlu et al., 2018). Due to the decrease of aggregate size, the increase of aggregate superficial area can promote the interaction between protein and solvent.…”
Section: Resultsmentioning
confidence: 99%
“…These mechanic forces have the ability to modify the aggregation state and conformation of proteins, and thus alter their functional property. Many food proteins have been processed by HPH to achieve targeted functionality (especially emulsifying and foaming properties), mainly including milk protein (Wang et al., 2020), legumes protein (Yang et al., 2018) and nut protein (Sarıcaoğlu et al., 2018). HPH treatment generally decreases particles into small size (Sarıcaoğlu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%